LEMBAGA PERKREDITAN DESA (LPD) DALAM PERSPEKTIF HUKUM : SEBUAH LEMBAGA KEUANGAN ADAT HINDU PENGGERAK USAHA SEKTOR INFORMAL DI BALI - Kurniasari, Tri Widya (Jurnal Masyarakat dan Budaya, 2025)
Lembaga Perkreditan Desa (LPD) as one of the Micro Finance Institutions has succeded in Province Bali in giving its service to the community. As an alternative finance institution, they have been able to reach the people with low income and small sized and micro business in informal sector. Unfortunatelly, LPD was build without the Governor of Indonesian Bank’s policy letter, which means that LPD has performed informally. This article attempts to analyze, not only about the management system of LPD which based on the Hindu-Bali values as the traditional customs and the major religion in Bali, but also the legal analysis on LPD itself, particularly after the Bali Bombings which have destroyed the economic sector in general. One of the findings in this article is that the service mechanism of LPD in Bali Province, which based on the value of local wisdom has became a major indicator in moving forward the economic growth. Keywords: Lembaga Perkreditan Desa, Bali, Informal Sector